2018
DOI: 10.1097/pec.0000000000001680
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Newborns Brought to the Emergency Department?

Abstract: Objectives Neonatal period is a peculiar life stage. This study aimed to characterize newborns' visits to the emergency department (ED) of a secondary care hospital. Methods Retrospective analysis of infants up to 28 days, who resorted to the ED between January and December of 2014, was performed. The data included newborn and maternal demographic characteristics and characterization of visits in the ED. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 11 publications
2
10
0
6
Order By: Relevance
“…Lower level of maternal education was independently associated with emergency room use for infants, though not with rehospitalization. Prior studies have demonstrated that socioeconomically disenfranchised groups are more likely to seek care for nonurgent medical problems in emergency rooms because of the lack of knowledge about appropriate use of emergency care, lack of health insurance, and/or access to timely outpatient care 26,27 …”
Section: Discussionmentioning
confidence: 99%
“…Lower level of maternal education was independently associated with emergency room use for infants, though not with rehospitalization. Prior studies have demonstrated that socioeconomically disenfranchised groups are more likely to seek care for nonurgent medical problems in emergency rooms because of the lack of knowledge about appropriate use of emergency care, lack of health insurance, and/or access to timely outpatient care 26,27 …”
Section: Discussionmentioning
confidence: 99%
“…(5) However most studies to date are limited by small numbers, and their applicability to our setting is unknown. (7) In Europe (8)(9)(10) and North America (5,11), up to one-third of neonates attending EDs have no medical issue, and a high proportion have low acuity problems requiring no medical investigation or treatment. Parents prefer to bring their children to either general (12) or paediatric (13) EDs, even with non-urgent problems, for reasons including parental anxiety, perceived advantages of EDs (resources and expertise), and convenience.…”
Section: Introductionmentioning
confidence: 99%
“…Millar (4) Londres, 2000 165.000 -2.750 Pérez Solís (2) Oviedo, 2000 21.258 --Pomerantz (23) Ohio, 2002 NR --Madden (26) Boston, 2002 NR --Jain (20) Atlanta, 2006 122585 --Fernández (27) Barcelona, 2006 77000 --Calado (10) Faro, 2009 36121 --Lara (5) Chile, 2014 24.531 --Lee (7) California, 2014 320540 -26711…”
unclassified
“…Batu (13) Ankara, 2014 28389 --Richier (11) Francia, 2015 23812 --Alfaro (8) Fuenlabrada, 2017 NR --Fornes (xx) Denia, 2017 8893 --Ijaz (12) Karachi, 2018 3115 --Ferreira (9 ) Guimaraes Casi dos neonatos de cada diez que nacen en nuestra maternidad acabará acudiendo cada año al SUP, valores no exagerados y semejantes a las comunicadas por otros países como USA (7) y España (8). Los neonatos suponen por otra parte solo un porcentaje pequeño del total de niños que acuden al SUP, aunque estas cifras son muy variadas según las características sociosanitarias y hospitalarias de cada país; las nuestras se asemejan a las de España ( 9), Portugal (10,11) y Francia ( 12) y se alejan de países como Pakistán y Turquía (5,13,14).…”
unclassified
See 1 more Smart Citation